Genomic and transcriptomic analysis of MSI-H colorectal cancer patients with targetable alterations identifies clinical implications for immunotherapy - Hua, Hanju; He, Wenguang; Chen, Nan; He, Yinjun; Wu, Guosheng; Ye, Feng; Zhou, Xile; Li, Yandong; Ding, Yongfeng; Zhong, Weixiang; Teng, Lisong; Jiang, Weiqin; et al. (Frontiers in Immunology, 2023)
Targetable alterations such as BRAFV600E mutation and NTRK fusion are enriched in microsatellite instability-high (MSI-H) colorectal cancer (CRC). MSI-H with targetable alterations (MSI-H altered) might present unique opportunities for both targeted therapy and immunotherapy. We systematically evaluated the molecular characteristics and immune-related features of MSI-H altered and MSI-H without targetable alterations (MSI-H wt) CRC patients in our study. Among 1938 continuously enrolled CRC patients, 126 patients with MSI-H status (6.50%) were included in this retrospective study. Genomic and transcriptomic data were investigated by next-generation sequencing (NGS) and gene expression profiling (GEP), respectively. BRAFV600E, NTRK1, and FGFR2 mutations were the most frequent targetable alterations in MSI-H CRC patients. The MSI-H altered phenotype was significantly associated with older age (p< 0.001), right side (p=0.024) and females (p= 0.036). No lynch syndrome (LS) patients were identified in MSI-H altered group. The tumor mutational burden (TMB), and tumor neoantigen burden (TNB) of MSI-H altered and wt subgroups were comparable (p>0.05). Subsequently, transcriptomic study analysis further revealed MSI-H altered CRC patients were linked to an immune-active tumor microenvironment with higher levels of Teff IFN-gamma, CYT, and MERCK 18 signatures, and lower levels of the IPRES gene signature, EMT and TGF Beta signatures. In addition, case study supported MSI-H CRC patient harboring targetable alterations might also achieved a long-term disease-free survival benefit from immunotherapy. Our study preliminary revealed MSI-H altered as a novel subtype of MSI-H CRC patients with unique molecular signatures and immune-active tumor microenvironment. Given the accessibility of immune checkpoint inhibitors (ICIs) treatment, our results might provide clinical evidence for immunotherapy in MSI-H CRC patients with targetable alterations.